Speech Acts in Wedding Ceremony Wurung Jue of Dayak Ma’anyan - Perdana, Indra; Emzir, Emzir (IJLECR (International Journal of Language Education and Cultural Review), 2016)
Wurung Jue is a series of events Process Dayak Customary Marriages Ma’anyan and Lawangan. Wurung jue Jue or bird is a symbol of faithful to their spouse. This research is a qualitative research. The main instrument in this study is the researchers themselves. Data collected over take the form of words or pictures instead of numbers. "The research data were retrieved through data collection techniques such as observation, interviews and documentation, namely the recording and record ripple used in ceremonies pernikahan.Hasil of this study were 1 ) ripple Ma’anyan Dayak is an old literary work because tumet a poem performed at the wedding customs Ma’anyan tribes commonly called Wurung Jue, 2) acts of speech commonly used in ripple namely locutions and illocutionary speech acts. Riak also has characteristics in common with each stanza rhyme that these ripples consist of four lines with end rhymes a-b-a-b. Each array consists of four words or eight with the provisions of the first two lines are always in the form of figurative or sampiran, while the content or the exact meaning contained in the third and four lines.